The medical ethics of Erasmus and the physician-patient relationship. Issue 1 (1st June 2001) - Albury, W R; Weisz, G M
Abstract : Desiderius Erasmus set out his views on medical ethics just over 500 years ago. Applying the characteristic approach of Renaissance Humanism, he drew upon a variety of classical sources to develop his own account of medical obligation. Of particular interest is Erasmus's attention to the patient's duties as well as the physician's. By treating this reciprocal relationship as a friendship between extreme unequals, Erasmus was able to maintain the nobility of the medical art and at the same time deal with the culturally sensitive issue of payment for physicians' services. The use of physician-patient reciprocity as a principle of medical ethics has until recently been considered a novel feature of nineteenth-century medical codes. As Erasmus's treatment of physician-patient reciprocity arose from a classical conception of friendship, there may be grounds for reconsidering the role of friendship in other discourses on medical ethics from the Renaissance to the nineteenth century.